Somatic ATM mutations indicate a pathogenic role of ATM in B-cell chronic lymphocytic leukemia - Schaffner, Claudia; Stilgenbauer, Stephan; Rappold, Gudrun; Döhner, Hartmut; Lichter, Peter (Blood, 1999)
Deletion in chromosome bands 11q22-q23 is one of the most common chromosome aberrations in B-cell chronic lymphocytic leukemia (B-CLL). It is associated with extensive lymph node involvement and poor survival. The minimal consensus deletion comprises a segment, which contains the ATM gene presenting an interesting candidate gene, as mutations in ATM predispose A-T patients to lymphoid malignancies. To investigate a potential pathogenic role of ATM in B-cell tumorigenesis, we performed mutation analysis of ATM in 29 malignant lymphomas of B-cell origin (B-CLL = 27; mantle cell lymphoma, [MCL] = 2). Twenty-three of these carried an 11q22-q23 deletion. In five B-CLLs and one MCL with deletion of one ATMallele, a point mutation in the remaining allele was detected, which resulted in aberrant transcript splicing, alteration, or truncation of the protein. In addition, mutation analysis identified point mutations in three cases without 11q deletion: two B-CLLs with one altered allele and one MCL with both alleles mutated. In four cases analyzed, theATM alterations were not present in the germ line indicating a somatic origin of the mutations. Our study demonstrates somatic disruption of both alleles of the ATM gene by deletion or point mutation and thus its pathogenic role in sporadic B-cell lineage tumors.
Online 14 December 2020
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 07.04.2021